Technical inefficiency, abatement cost and substitutability of industrial water pollutants in Jiangsu Province, China. (20th January 2021) - Yu, Qian-wen; Wu, Feng-ping; Zhang, Zhao-fang; Wan, Zhong-chi; Shen, Jun-yuan; Zhang, Li-na
Abstract: Environmental pollution, caused by industrial wastewater discharge, restricts the transformation of China's industrial economy. In terms of its gross industrial product, Jiangsu Province has always been among the top-ranking areas of China. To ensure the green and sustainable development of Jiangsu's industry, it is imperative to formulate specific strategies toward the reduction of industrial water pollutant emissions. First, by the parameter quadratic directional output distance function and the shadow price model, this paper estimates the technical inefficiency and marginal abatement costs of industrial chemical oxygen demand (COD) and ammonia nitrogen (NH3 –N) in Jiangsu Province between 2006 and 2017. Second, spatial and temporal distributions as well as the dynamic evolution tendencies of technical inefficiency, and abatement costs of industrial COD and NH3 –N are analyzed. Third, the Morishima elasticity model is utilized to measure the output substitution elasticity of industrial COD and NH3 –N for Jiangsu. The results show that the technical inefficiency of industrial water pollutants in Jiangsu Province followed a decreasing trend from 2006 to 2017; moreover, significant differences were found in technical inefficiency among different regions. Over time, the regional disparity followed a polarization trend. For Jiangsu Province, the marginal abatement cost of industrial COD increased rapidly and continuously, while the marginal abatement cost of industrial NH3 –N showed fluctuating and marginal growth from 2006 to 2017. The marginal abatement cost of industrial COD in southern Jiangsu exceeded that of other regions; however, the marginal abatement cost of industrial NH3 –N in northern Jiangsu was highest. Additionally, the negative sign of the Morishima output elasticity for Jiangsu indicates a "trade-off" relationship between gross industrial output and industrial water pollutants. Finally, according to the empirical results, corresponding policy recommendations are proposed. Highlights: This study analyzed the technical inefficiency of industrial water pollutants. The quadratic directional distance function was used to analyze this efficiency. The shadow price model was used to calculate the abatement costs of pollutants. Morishima elasticity was used to assess the output substitutability of pollutants. Differentiated emission reduction policies should be adopted in Jiangsu.